Dirty Electricity. - Grier, David Alan (Computer (00189162), 2007)
The article discusses the idea of "debugging" in computer software and hardware engineering. According to the author, the concept of a bug in engineering issues can be traced to Thomas Edison who used the term to describe problems with electrical systems. The article defines debugging as the process of removing conceptual errors from programs. The concept of debugging has always been a large part of a computer programmer's job, however, no extensive research or theory exists for the debugging process. An account of debugging problems had by a small engineering firm is included in the article.